The effect of kinetic prediction on some mental and physical abilities of handball goalkeepers - Shawkat Ibrahim, Hatem; Lateef Challoob, Hasan; Saad Ahmed, Omar (International Journal of Psychosocial Rehabilitation, 2020)
The study aimed to identify the relationship between motor expectation and some mental abilities of the goalkeeper as well as the relationship between motor expectation and some physical attributes of the goalkeeper.